Social Conflict and Covid-19 (Case Study of Religious Activities in Parepare) - Muhammad Fajar; A. Nurul Mutmainnah; Abd Rasyid (SOSIOLOGIA : Jurnal Agama dan Masyarakat, 2022)
The life of the religious community cannot be separated from religious activities in this case the Covid-19 pandemic in religious activities did not escape social changes in religious communities, especially in the City of Parepare. Thus, in this study trying to analyze the conflicts and power relations that occur in the community with various religious activities from various existing religions. This research is a qualitative method with a data approach in the form of narratives, stories, expressions from informants. Meanwhile, the type of research used is a case study. Informants in the research based on the needs in this study include religious leaders, government officials, the community and discourses that narrate about conflicts and power relations.Research shows that during the COVID-19 pandemic, the ideal of worshiping in congregation has changed drastically. Routine worship is no longer carried out in mosques, churches, or monasteries but is carried out in their respective homes. The people involved are also very limited, in this case it only involves family members who are at home. Based on knowledge and power, it is also closely related to the power relations between the government, religious leaders, and the community. The condition of the COVID-19 pandemic requires an open and “flexible” attitude for religious people to combine two different interests. When religious teachings command to worship communally in the face of various government regulations, many things should be compromised.